Discussion [Sands M. "Observation of quantum effects in an electron synchrotron"]; International conference on highenergy accelerators and instrumentation - Cern 1959 (Geneva, 14th-19th September, 1959) - Worobjow А. А. Alexander Akimowitsch (1959, 1959)
В фонде НТБ ТПУ отсутствует